1986
DOI: 10.1021/bi00367a036
|View full text |Cite
|
Sign up to set email alerts
|

Galactose-1-phosphate uridylytransferase. Purification of the enzyme and stereochemical course of each step of the double-displacement mechanism

Abstract: A convenient new procedure for purifying galactose-1-phosphate uridylyltransferase from Escherichia coli is described. It departs from earlier methods by introducing the use of a Cibacron Blue-agarose (Bio-Rad Affi-Gel Blue) at an early stage. Purification is completed by ion-exchange chromatography using DEAE-Sephadex A-50. The procedure is substantially shorter than earlier methods and reproducibly yields enzyme of high specific activity suitable for use in structural work such as characterization of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…In the cascade of activation steps for glutamine synthetase, for example, the activity of P II protein is controlled by its degree of uridylylation, which in turn controls glutamine synthetase activity (1,28). Furthermore, the interconversion of galactose-1-phosphate and glucose-1-phosphate occurs in their uridylylated forms, using uridylyl transferase as a covalent intermediate (5,16). In the P II protein, a tyrosine residue serves as the acceptor for the uridylate residue (1,59), whereas with uridyl transferase in galactose metabolism, a histidine is the uridylate acceptor (64).…”
Section: Discussionmentioning
confidence: 99%
“…In the cascade of activation steps for glutamine synthetase, for example, the activity of P II protein is controlled by its degree of uridylylation, which in turn controls glutamine synthetase activity (1,28). Furthermore, the interconversion of galactose-1-phosphate and glucose-1-phosphate occurs in their uridylylated forms, using uridylyl transferase as a covalent intermediate (5,16). In the P II protein, a tyrosine residue serves as the acceptor for the uridylate residue (1,59), whereas with uridyl transferase in galactose metabolism, a histidine is the uridylate acceptor (64).…”
Section: Discussionmentioning
confidence: 99%
“…The most common form of galactosemia arises from defects in galactose-1-phosphate uridylyltransferase and as such it has been the subject of intensive kinetic and structural investigations for many years (Holden et al 2003). Studies have demonstrated that the reaction mechanism of this enzyme proceeds through a covalently bound intermediate via a double displacement pathway (Arabshahi et al 1986). …”
mentioning
confidence: 99%
“…In the second-half reaction, Gal-1-P enters the active site cleft and attacks the uridylylated nitrogen on the imidazole ring of the active site histidine, forming UDP-Gal. This second product then dissociates, regenerating free enzyme (2,7).…”
mentioning
confidence: 99%